A review of long non-coding RNAs in ankylosing spondylitis: pathogenesis, clinical assessment, and therapeutic targets - Wang, Hanji; Yang, Chengxian; Li, Ge; Wang, Boning; Qi, Longtao; Wang, Yu (Frontiers in Cell and Developmental Biology, 2024)
Ankylosing spondylitis (AS) is a chronic immune-mediated type of inflammatory arthritis characterized by inflammation, bone erosion, and stiffness of the spine and sacroiliac joints. Despite great efforts put into the investigation of the disease, the pathogenesis of AS remains unclear, posing challenges in identifying ideal targets for diagnosis and treatment. To enhance our understanding of AS, an increasing number of studies have been conducted. Some of these studies reveal that long non-coding RNAs (lncRNAs) play crucial roles in the etiology of AS. Some certain lncRNAs influence the development of AS by regulating inflammatory responses, autophagy, apoptosis, and adipogenesis, as well as the proliferation and differentiation of cells. Additionally, some lncRNAs demonstrate potential as biomarkers, aiding in monitoring disease progression and predicting prognosis. In this review, we summarize recent studies concerning lncRNAs in AS to elucidate the underlying mechanisms in which lncRNAs are involved and their potential values as biomarkers for disease assessment and druggable targets for therapy.